2021
DOI: 10.3390/nu13010180
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in Infectious Diseases in Older People

Abstract: Reduced magnesium (Mg) intake is a frequent cause of deficiency with age together with reduced absorption, renal wasting, and polypharmacotherapy. Chronic Mg deficiency may result in increased oxidative stress and low-grade inflammation, which may be linked to several age-related diseases, including higher predisposition to infectious diseases. Mg might play a role in the immune response being a cofactor for immunoglobulin synthesis and other processes strictly associated with the function of T and B cells. Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 179 publications
3
69
0
Order By: Relevance
“…Mg deprivation, low serum Mg levels, and reduced dietary Mg intake have all been associated in preclinical, epidemiological and clinical human studies with an increased production of free radicals of oxygen, with low-grade systemic inflammation, increased levels of inflammation markers and proinflammatory molecules (IL-6, tumor necrosis factor-alpha (TNF-alfa), IL-1-beta, vascular cell adhesion molecule (VCAM)-1, and plasminogen activator inhibitor (PAI)-1, complement, alfa2-macroblobulin, fibrinogen) [16,[35][36][37][38][39][40][41][42].…”
Section: Mg Inflammation and Oxidative Stressmentioning
confidence: 99%
“…Mg deprivation, low serum Mg levels, and reduced dietary Mg intake have all been associated in preclinical, epidemiological and clinical human studies with an increased production of free radicals of oxygen, with low-grade systemic inflammation, increased levels of inflammation markers and proinflammatory molecules (IL-6, tumor necrosis factor-alpha (TNF-alfa), IL-1-beta, vascular cell adhesion molecule (VCAM)-1, and plasminogen activator inhibitor (PAI)-1, complement, alfa2-macroblobulin, fibrinogen) [16,[35][36][37][38][39][40][41][42].…”
Section: Mg Inflammation and Oxidative Stressmentioning
confidence: 99%
“…The overall prevalence of hypomagnesemia in geriatric patients reaches 36% [ 30 ], among diabetic patients ranges from 19% to 29% [ 31 , 32 ], and in patients with high blood pressure, it has been found to be 63.8% [ 33 ]. In addition, it has been reported that magnesium deficiency is associated with obesity and the increased incidence of hypertension, cardiovascular disease, congestive heart failure, arrhythmias, and chronic kidney disease, particularly in patients under dialysis [ 34 36 ]. Furthermore, it has been noted that mortality by cardiovascular deaths in subjects with hypomagnesemia is significantly higher as compared with individuals exhibiting normal magnesium levels [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the fundamental importance of magnesium in immunity and the underlying mechanisms have been highlighted by the discovery of the primary immunodeficiency XMEN (X-linked immunodeficiency with magnesium defect, Epstein–Barr virus infection, and neoplasia), which is characterized by chronic Epstein-Barr virus infection [ 51 ]. However, general evidence that magnesium deficiency may confer a higher predisposition to infectious diseases is mostly indirect [ 34 ]. An optimal magnesium status is necessary for the synthesis, transport, and activation of vitamin D [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have explored the importance to supplement Mg for increasing vitamin D levels in postmenopausal women [11] and for improving several cardiovascular biomarkers [12]. These novel findings could partly explain the role of Mg in improving outcomes in infectious diseases [13] and for improving hypertension [14], one of the most common condition in older subjects, as discussed in two reviews. Furthermore, the correct assessment of Mg status, particularly in older people, is often problematic.…”
mentioning
confidence: 99%